Legal Review of the Attorney General's Authority in Carrying Out Asset Recovery of the Proceeds of Money Laundering Crimes - Ade Onny Siagian; ST Laksanto Utomo; Joko Sriwidodo (Law and Justice research journal, 2026)
Money laundering is a derivative crime that is frequently associated with corruption and has the potential to cause significant losses to state finances. Efforts to recover assets derived from criminal activities constitute an essential aspect of law enforcement aimed at restoring state losses and creating a deterrent effect for perpetrators. This study aims to analyze the authority of public prosecutors in the investigation of money laundering crimes as well as the mechanisms for state asset recovery based on the authority of the Indonesian Attorney General’s Office. The research method employed is normative juridical research using statutory and case approaches. The results of this study indicate that the Attorney General’s Office possesses clear and legally valid authority to conduct investigations into money laundering crimes as regulated under Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering and the Law on the Attorney General’s Office. Prosecutors are authorized to trace, seize, confiscate, and recover assets derived from criminal acts without first proving the predicate offense. This study further emphasizes that although the authority of the Attorney General’s Office has been normatively regulated, in practice, state asset recovery continues to face various obstacles, both in substantive and procedural law, such as inconsistencies in statutory regulations and the suboptimal implementation of non-conviction-based asset forfeiture. Therefore, strengthening regulations and harmonizing legal policies are necessary to ensure that state asset recovery through the handling of money laundering crimes can be carried out more effectively and provide legal certainty.